2017
DOI: 10.1093/aob/mcx179
|View full text |Cite
|
Sign up to set email alerts
|

Origin of C. latifolia and C. aurantiifolia triploid limes: the preferential disomic inheritance of doubled-diploid ‘Mexican’ lime is consistent with an interploid hybridization hypothesis

Abstract: The doubled-diploid 'Mexican' lime had predominantly disomic segregation, producing interspecific diploid gamete structures with high C. medica/C. micrantha heterozygosity, compatible with the phylogenomic structures of triploid C. latifolia and C. aurantiifolia varieties. This disomic trend limits effective interspecific recombination and diversity of the diploid gamete population. Interploid reconstruction breeding using doubled-diploid lime as one parent is a promising approach for triploid lime diversifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 89 publications
(128 reference statements)
10
35
0
1
Order By: Relevance
“…The gamete proportions explained by random meiotic chromosome association (τ) ranged from 7 to 58%, and for all markers preferential pairing occurred between chromosomes derived from the same parent (i.e., WLM or PON). Such intermediate inheritance with a disomic tendency was also described for a doubled-diploid “Mexican lime” ( Rouiss et al, 2018 ) belonging to C. x aurantiifolia (Christm.) Swingle, a species of interspecific origin ( C. micrantha Wester x C. medica L.; Nicolosi et al, 2000 ; Curk et al, 2016 ; Wu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The gamete proportions explained by random meiotic chromosome association (τ) ranged from 7 to 58%, and for all markers preferential pairing occurred between chromosomes derived from the same parent (i.e., WLM or PON). Such intermediate inheritance with a disomic tendency was also described for a doubled-diploid “Mexican lime” ( Rouiss et al, 2018 ) belonging to C. x aurantiifolia (Christm.) Swingle, a species of interspecific origin ( C. micrantha Wester x C. medica L.; Nicolosi et al, 2000 ; Curk et al, 2016 ; Wu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 52%
“…For the last somatic hybrid, this cytogenetic observation was associated with preferential tetrasomic inheritance of molecular markers. However, as previously mentioned, reciprocal or inverted translocations can result in tetravalent formation even in diploid parents as observed in “Valencia” sweet orange ( Del Bosco et al, 1999 ) or Mexican lime ( Rouiss et al, 2018 ). Therefore, cytogenetic observations should be associated with marker segregation analysis for a full understanding of tetraploid meiosis behavior.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Navarro et al (2015) showed that the 'Fortune' mandarinwhen used as a female parent -produced a greater frequency of triploid hybrids per fruit than clementines. In citrus cultivars, triploid hybrids have been successfully used to produce seedless fruits (Aleza et al, 2012;Rouiss et al, 2018). Despite their desirable characteristics, such as larger fruit and higher yield (Hoshino et al, 2011), triploid plants are unusual because of their inviable seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, we found that for 'Moncada' mandarin as female parent, the LG6 shows tetrasomic segregation, while results for the LG8 agree with the after as was reported for the tetraploid 'Clemenules' clementine, but with higher PP value. Subsequently, Rouiss et al (2018) analyzed the segregation model of the tetraploid 'Mexican' lime (C. aurantiifolia), which originated from an interspecific hybridization between C. micrantha (papeda) and C. medica (Citron) (Curk et al 2016;Nicolosi et al 2000;Wu et al 2018). The results showed that tetraploid 'Mexican' lime has intermediary inheritance with a preferential disomic trend.…”
Section: Preferential Pairing (Pp) and Maximum Double Reduction (Dr)mentioning
confidence: 99%